Effect of ultrasonic surface rolling process on the fretting tribocorrosion behaviors of Inconel 690 alloy. (June 2023) - Yin, Meigui; Zhang, Lei; Huang, Longxiang; Zhang, Xiaofeng
Abstract: The ultrasonic surface rolling process (USRP) is conducted by making the metal surface undergo micro-plastic deformation to improve its surface state and some mechanical properties, thus strengthening its tribocorrosion resistance. In this study, the surface of the Inconel 690 alloy block was treated by special USRP, and the change in its tribocorrosion behaviors had been effectively revealed by a fretting electrochemical corrosion test rig. Results showed that the Inconel 690 alloy's tribocorrosion degree and corrosion rate were evidently reduced after USRP. These results could be attributed to the surface finish reduction and surface grain refinement caused by USRP.